SELECTED PROBIOTIC PARAMETERS OF LACTIC ACID BACTERIA ISOLATED FROM THE FAECES OF VEGETARIANS AND NONVEGETARIANS (Fiep Bulletin - online, 2014)
In this work were isolated about 80 strains of lactic acid bacteria from the faeces of young (21-30 years) and older (51-60 years) vegetarians and nonvegetarians. The identification of isolated strains was based on their morphological and biochemical properties. The following probiotic properties were determined: survival at low pH value, and bile salt hydrolase activity. The isolated strains belong to lactobacilli, bifidobacteria, enterococci and propionibacteria. All strains were negative in bile salt hydrolase activity, but the growth in the presence of bile was not inhibited. The results from the study of survival at low pH showed considerable variability in both dietary groups regardless the age of probands.  Acknowledgments: This article was part of the project funded by the Agency of the Ministry of Education, Science, Researchand Sport of The Slovak Republic for EU Structural Funds ITMS 26240220040 and ITMS 26240220022.
Keywords: gastrointestinal tract; probiotic bacteria; vegetarians; nonvegetarians